CSF β-amyloid predicts prognosis in patients with multiple sclerosis. (August 2019) - Pietroboni, Anna M; Caprioli, Michela; Carandini, Tiziana; Scarioni, Marta; Ghezzi, Laura; Arighi, Andrea; Cioffi, Sara; Cinnante, Claudia; Fenoglio, Chiara; Oldoni, Emanuela; De Riz, Milena A; Basilico, Paola; et al.
Background: The importance of predicting disease progression in multiple sclerosis (MS) has increasingly been recognized, and hence reliable biomarkers are needed. Objectives: To investigate the prognostic role of cerebrospinal fluid (CSF) amyloid beta1–42 (Aβ) levels by the determination of a cut-off value to classify patients in slow and fast progressors. To evaluate possible association with white matter (WM) and grey matter (GM) damage at early disease stages. Methods: Sixty patients were recruited and followed up for 3–5 years. Patients underwent clinical assessment, brain magnetic resonance imaging (MRI; at baseline and after 1 year), and CSF analysis to determine Aβ levels. T1-weighted volumes were calculated. T2-weighted scans were used to quantify WM lesion loads. Results: Lower CSF Aβ levels were observed in patients with a worse follow-up Expanded Disability Status Scale (EDSS; r = −0.65, p < 0.001). The multiple regression analysis confirmed CSF Aβ concentration as a predictor of patients' EDSS increase ( r = −0.59, p < 0.0001). Generating a receiver operating characteristic curve, a cut-off value of 813 pg/mL was determined as the threshold able to identify patients with worse prognosis (95% confidence interval (CI): 0.690–0.933, p = 0.0001). No differences in CSF tau and neurofilament light chain (NfL) levels were observed ( p > 0.05). Conclusion: Low CSF Aβ levels may represent a predictive biomarker of disease progression in MS.